Experimental specification of the nature of rock mass fragmentation by blasting of borehole charges of variable length - Titov, Danyl; Zahorsky, Dmytro; Hryhoriev, Yulian; Balyk, Serhii; Kozariz, Volodymyr (Technology audit and production reserves, 2025)
The object of this study is the process of rock mass destruction in open-pit mines during large-scale blasting operations using borehole charges of variable length. The deficiencies identified during the experimental audit include the discrepancy between the particle size distribution of the blasted rock mass and the design parameters. This mismatch is particularly evident under conditions of geogenic and anthropogenic disturbances, zones with variable bench heights, and contacts between different types of rock. One of the most problematic areas includes sections with developed fracture systems, which influence the propagation of blast waves and lead to zones of anomalous destruction and increased proportions of oversized rock fragments. The inconsistency between the actual and calculated particle size distribution of the blasted rock mass in disturbed rock bodies complicates the design of blasting operations and the execution of technological processes in open-pit mining. This challenge becomes even more significant when mining activities are conducted in close proximity to urban development. The research utilized experimental blasting methods, stepwise excavation with photographic documentation, and visual analysis of fragmentation zones, taking into account the length of charges and detonation delays. A qualitative outcome was achieved: the hypothesis regarding the regularities in the formation of volumetric zones in the rock mass was confirmed. Within these zones, the rock mass fragmented by the blast exhibits a relatively uniform particle size distribution. It was established that the key factors influencing the efficiency of explosive fragmentation in heterogeneous rock masses are the degree of natural fracturing and the detonation velocity (brisance) of the explosives. Observations from the layer-by-layer excavation of the fragmented rock partially confirmed the predicted effects of intentional variation in delay times between charges within groups of blast boreholes. As a result, the blasting process becomes more technologically controllable, leading to improved granulometric composition of the rock mass and a reduction in the proportion of oversized material. Compared to traditional blasting schemes, the use of variable-length borehole charges allows for more effective adaptation to the complex structure of the rock mass and to conditions involving proximity to urban infrastructure, thereby providing technical and economic advantages in open-pit mining operations.